Use of UTAUT for analyzing the acceptance and use of electric scooters in the public transport system - Fernando Marroquín-Ciendúa; Manuel Medina-Labrador; Laura Camila Hurtado Méndez; Lorena Patricia Mora Hernández; Cristian Nicolás Puentes Guzmán (Urban, Planning and Transport Research)
.Bogotá’s Urban transport system faces critical challenges due to 80% population growth, insufficient routes, and a limited culture of solidarity. These factors exacerbate travel times, congestion, pollution, and user stress. Electric scooters (SES) have been introduced to mitigate these issues but remain underutilized. This study identifies factors that could enhance scooter adoption in Chapinero, Bogotá. The research was conducted in three phases: (1) Descriptive phase, a qualitative study with in-depth interviews, Exploratory Factor Analysis, and Principal Component Analysis; (2) Correlational phase, a statistical validation of the UTAUT model using survey responses from 424 participants; (3) Predictive phase, two Binary Logistic Regressions and a Log-Linear Analysis assessed the relationships between independent variables (Gender, Socioeconomic Strata, Incentives, and Knowledge of Scooters) and the dependent variable (Scooter Use). Results indicate that without prior knowledge or incentives, the probability of scooter use is just 1.59%. However, prior knowledge alone raises adoption likelihood to 71.14%, while additional incentives, such as gamification and point-based rewards, increase it to 90.37%. These findings provide insights for policymakers and mobility service providers to enhance sustainable urban transport in Bogotá.